The Use of Phrases in Writing Descriptive Text by The Students of SMA Negeri 1 Boyolali In 2015/2016 Academic Year - Wijayanti, Intan (2016)
This research focuses on analyzingthe use of phrases in writing descriptive text by the students of sma negeri 1 boyolali 2015/2016 academic year. The objectives are to describe the students' ability in writing of phrases in descriptive text, to know the dominant phrase found in descriptive text made by student, and to describe the construction of phrases used by the students.This research applies descriptive qualitative method. The data and data sourcearethe phrases written by the twelfth grade students of IIS 2. The ways to collect data are by using docummentation, task, and documentation. The results of the research show that, firstly, the ability of the twelfth grade students of SMA Negeri 1 Boyolali in writing phrases of descriptive text was very good. It can be seen from the percentage of total correct phrases (92.15%) to the total incorrect phrases (7.85%). The highest incorrect phrase made by the students was on the verb phrase. They totally produced 216 verb phrases with 165 correct phrases and 51 incorrect phrases. The students used all five phrases in writing descriptive text namely noun phrase, verb phrase, adjective phrase, adverb phrase and prepositional phrase.The dominant phrase found in writing phrases of descriptive text written by the twelfth grade students of SMA Negeri 1 Boyolali was noun phrase (47.94%). The writer found many constructio of phrases made by the students in writing descriptive text with the theme of historical places. They produced 43 construction of noun phrase, two construction of verb phrase, adjective phrase of complementation, adverb phrase, and prepositional phrase